2011
DOI: 10.1080/17470218.2011.594165
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers' Language-Mediated Visual Search: They Need not have the Words for It

Abstract: Eye movements made by listeners during language-mediated visual search reveal a strong link between visual processing and conceptual processing. For example, upon hearing the word for a missing referent with a characteristic colour (e.g., “strawberry”), listeners tend to fixate a colour-matched distractor (e.g., a red plane) more than a colour-mismatched distractor (e.g., a yellow plane). We ask whether these shifts in visual attention are mediated by the retrieval of lexically stored colour labels. Do childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 22 publications
1
60
4
Order By: Relevance
“…In their studies using the IPL method, Styles and Plunkett () found a priming effect in 24‐month‐olds but not 18‐month‐olds, and Arias‐Trejo and Plunkett () found a priming effect in 21‐month‐olds but not in 18‐month‐olds. Other research has found that 24‐month‐olds activate properties (such as color) or a word's meaning when they hear that word (Johnson, McQueen, & Huettig, ; Swingley & Fernald, ). Because of the novelty of our method, and especially due to the removal of all contextual cues to a word's meaning, we studied 24‐month‐olds in order to ensure that participants had the requisite knowledge for the task.…”
Section: Methodsmentioning
confidence: 99%
“…In their studies using the IPL method, Styles and Plunkett () found a priming effect in 24‐month‐olds but not 18‐month‐olds, and Arias‐Trejo and Plunkett () found a priming effect in 21‐month‐olds but not in 18‐month‐olds. Other research has found that 24‐month‐olds activate properties (such as color) or a word's meaning when they hear that word (Johnson, McQueen, & Huettig, ; Swingley & Fernald, ). Because of the novelty of our method, and especially due to the removal of all contextual cues to a word's meaning, we studied 24‐month‐olds in order to ensure that participants had the requisite knowledge for the task.…”
Section: Methodsmentioning
confidence: 99%
“…One important question for further research is how we transition from a prelinguistic color categorization based largely on biological mechanisms to a lexical color categorization that may make additional or fewer distinctions. The lack of one-to-one mapping between prelinguistic and lexical color categorization may well partly explain the difficulty that children have in learning the words for colors (49)(50)(51)(52). Further research should also examine whether the distinctions in infant color memory are universal across different cultures and environments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on infants’ lexical development suggests that infants’ lexicons are organized in a network with groupings based on taxonomic, perceptual, functional, and associational relationships from as early as 14 months (Friedrich & Friederici, ) and continue to develop into the second year of life (Arias‐Trejo & Plunkett, , , ; Johnson & Huettig, ; Johnson, McQueen, & Huettig, ; Mani, Johnson, McQueen, & Huettig, ; Styles & Plunkett, ). Such clustering characterizes adult lexicons and may be considered a proper developmental achievement.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson et al. () also clarified with 2‐year‐old participants that color label comprehension is not required for this effect. On the other hand, in a similar experiment (Huettig & Altmann, ), adult participants were more likely to fixate on color‐associated distracters than at other distracters only when the pictures were presented in color.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation